EXPERIMENTAL STUDY OF HORIZONTAL PRESSURE DISTRIBUTION ON CORRUGATED STEEL SILO WALLS - Kachurenko, V. V.; Bannіkov D. O. (Science and Transport Progress, 2016)
Purpose. The paper aims: 1) qualitative assessment of the nature of the container corrugated wall deformation caused by the load from bulk materials. 2) determination of the horizontal pressure redistribution scheme for each individual corrugation plate and the calculation method that is closer to the real situation. 3) obtaining the quantitativedeformation indicators to compare them with the calculated ones produced by means of mathematical model simulation. Methodology.To achieve this purpose the different types of capacitive structure profiles were investigated and the values of total vertical displacement under load were obtained. The computational experiment used the design computer system Structure CAD for Windows. In addition, the laboratory experiment was conducted, the analysis of which is important to confirm the correctness of pre-made computer models. Findings. The conducted experiment allowed receiving the confirmation of the FEM calculated data, namely qualitatively and quantitatively the deformation direction and nature completely repeated the design situation in SCAD. Thework ofcorrugatedprofile was analysedfordifferenttheoreticallypossibleload schemesanddifferentcalculation methods. Alsotheworkcontainstherecommendationsfortherealcalculationusingcomputersimulation. During a joint study the authors obtained the data that allow for more accurate assessment of the corrugated profile performance under the pressure from bulk materials. Originality. The conducted research and experimental tests explain and clarify the ways for possible redistribution of bulk material pressure on each corrugation plate, while there is no such information in the existing recommendation literature and regulatory framework concerning the capacitive structure design. Practical value.The use of the proposed solutions is useful for correct design of containers with corrugated walls during further calculations and search of new directions for future research.